Synthesis and Structural Investigation of Mixed Ligand Metal Complexes of Isonitroso-p-methyl Acetophenone and Dienes - Jadhao, S.Z.; Raut, R.D.; Saraf, B.D. (Asian Journal of Chemistry, 2016)
Studies of the complexes of metal ions with p-methyl acetophenone and dienes have been carried out on the basis of elemental analysis, molar conductance, electronic spectra etc. The complexes have been assigned to formula M2(APPD)2 (M = Co, Ni or Cu).